P1-S6.11 Prevention of mother to child transmission of HIV (PMTCT) program in Burkina Faso: how high is the coverage of voluntary counselling and HIV Testing (VCT) services within a clinical trial supporting environment?. (10th July 2011) - Traore, H A; Some, E; Meda, N; Nagot, N; Van De Perre, P
Abstract : Background: Since 2003, Burkina Faso has set up a national PMTCT program. Programme monitoring 2009 annual report showed high health districts and facilities coverage. But at beneficiaries' level, how many women and children in need of PMTCT interventions have really access? The objective of our study was to measure the uptake of VCT with a comprehensive set of data collected in the recruitment process in a clinical trial evaluating postnatal chemoprophylaxis to reduce MTCT. Methods: We carried out a cross-sectional study from 1 January 2010to 31 December 2010 in 26 out of 35 PMTCT sites in five health districts in Ouagadougou city. Weekly data collection in PMTCT registers and semi-structured interviews with the personals in charge of MCH departments. Results: Among the 44 484 new recorded Antenatal care (ANC) attendees, 37 539 received HIV counselling and 37 489 were tested for HIV (results returned immediately), an acceptance rate of 99, 86%. 6, 945 new ANC did not profit from the HIV counselling equalling 15.61% of the participant population. This miss opportunity for VCT was related to test supplies out of stock (78%), lack of VCT offer due to opt in strategy still in place in many facilities (17%) and structural problems (no trained staff, lack of infrastructures) in the remaining cases. Conclusion: Our results underline the overall good performance of the PMTCT program in the context of a clinical trial facilitating environment. However, a better organization of the supply procurement would allow improving VCT coverage rate. With this high coverage of VCT in research context, we can assume that the low VCT coverage at program (75%) level is mainly due to healthcare system problem.